Assessment the Role of Sediment in the Sumber Brantas Rivers Watershed Affected by Agroforestry Activities - Barlah Rumhayati; Hari Siswoyo; MH. Chusnuddin Nurochman (Institut Teknologi Sepuluh Nopember, 2014)
Assessment the role of sediment in the Sumber Brantas River watershed has been conducted in Sumber Brantas, Bumiaji, Batu. The area has been affected by agroforestry activities. The assessment was focused to the availability of nutrients (phosphorous and nitrogen compounds) and metals in sediment and water column. Water and sediment samples were collected from outlet Sumber Brantas watershed in Arboretrum, Sumber Brantas, Bumiaji, Batu, Malang in July 2013. Assessment of physical and chemical water properties included pH, conductivity, temperature, TDS, DO, COD, total P and reactive P, nitrate and ammonia, dissolved metals (Al, Fe, Mn, Ca, Mg). Meanwhile, the assessment of physical and chemical properties of sediment included texture, porosity, density, pH, redox potensial, DO, organic matter, N and P sediment solution, total metals, and exchangeable metals. Results showed that water body of Sumber Brantas watershed was oxic. The level of nitrate in wPater bodies was higher than ammonia level due to nitrification process while the level of FRP was low. Most of P in the water bodies were adsorbed onto oxide/hydroxide metals and bound to metals. The sediment was at anoxic condition. The immediately pool of P was lower than the potential P pools. The level order of sedimentary inorganic P in the sediment was residual-P > HCl-P > BD-P > NaOH-P> NH4Cl-P. Although the level of DO in sediment was low so that the denitrification was occurred but the P could not easily released from the FeOOH surface. The complex of FeOOH-P in sediment was stable to be dissociated so P was not released into water bodies even under anoxic condition. Therefore, the role of sediment of the Sumber Brantas River watershed was as a for P compounds while nitrate in the sediment was subjected to change and equilibrate with ammonia.